Improving family engagement during implementation of IEP-aided AAC services: an interdisciplinary US-based perspective - Erwin-Davidson, Lisa; McKee, Aja; O’Crowley, Erin (Frontiers in Education, 2024)
All IEP team members should find statements pointing to where and when the aided AAC system and accessible learning tools will be used. Classroom-based and research supported AAC learning strategies and teaching practices (Quinn, Kurin et al., 2023;Taub et al., 2017) should be clearly listed, explained, and accessible to all team members. Aided AAC refers to a variety of communication tools that are portable and external to the body. Aided AAC ranges from paper-based picture communication cards, boards, binders, tablets, or digital smartphone applications to multifunctional/high-tech devices offering synthesized and digitized speech. Aided AAC allows students with CCN/ESNs to access speech or writing using any body part capable of performing voluntary and independent movement. Many electronic/high-tech aided AAC systems can store thousands of multilingual words, allowing seamless communication between home and school. Students with CCN/ESNs can also use hightech aided AAC with native keyboards as "alternative pencils" to practice spelling and early writing, thus allowing equitable academic access and opportunities to make progress on emergent literacy skills (Benson-Goldberg & Erickson, 2024;Light et al., 2021;Light & Kent-Walsh, 2003).High-tech/digital-aided AAC allows for the maturation of linguistic specificity and fuller participation in daily routines required for academic success. It is critical for students with CCN/ESNs to use high-tech aided AAC with ample vocabulary storage to increase opportunities for self-generation of complex and decontextualized messages for varied social interactions. Additionally, digital device platforms (e.g., iPads, other tablets, Smartphones) offer multiple